Ultra-high thermally conductive and rapid heat responsive poly(benzobisoxazole) nanocomposites with self-aligned graphene. Issue 48 (24th October 2016) - Zhao, Weifeng; Kong, Jie; Liu, Hu; Zhuang, Qiang; Gu, Junwei; Guo, Zhanhu
Abstract : Aligned graphene sheets resulted in highly anisotropic thermal conductive PBO nanocomposite films with ultra-high in-plane thermal conductivity. Abstract : Self-alignment of thermally reduced graphene sheets (TRG) that enable highly efficient heat transfer paths in their poly( p -phenylene benzobisoxazole) (PBO)-based nanocomposite films along the in-plane direction was achieved for the first time without any assistance of an external magnetic or an electric field. In the in-plane direction, the nanocomposite films possess an ultra-high thermal diffusivity (900–1000 mm 2 s −1 ) and a thermal conductivity (50 W m −1 K −1 ) with a TRG concentration <5.0 vol%, setting a new record for polymer composites with such a low graphene filler loading. The arranged TRG was also found to display a high efficiency for PBO reinforcement. A 64% increase in the Young's modulus was achieved by the addition of only 0.35 vol% of TRG, corresponding to a reinforcement value as high as 747 ± 38 GPa, due to effective load transfer between the PBO matrix and TRG sheets via strong interfacial interactions. Moreover, the highly ordered graphene in PBO could provide good candidates for effective heat shielding barriers, and thus the prepared PBO composites exhibit a thermal stability remarkably higher than that of neat PBO resin.